2014
DOI: 10.4103/0973-1296.126671
|View full text |Cite
|
Sign up to set email alerts
|

Optimal inductive and cultural conditions of Polygonum multiflorum transgenic hairy roots mediated with Agrobacterium rhizogenes R1601 and an analysis of their anthraquinone constituents

Abstract: Background:Polygonum multiflorum is an important medicinal plant. Hairy roots systems obtained by transforming plant tissues with the natural genetic engineer Agrobacterium rhizogenes can produce valuable biological active substances, which have immense potential in the pharmaceutical industry.Objective:To optimize the inductive and cultural conditions of P. multiflorum hairy roots and to identify the major active secondary metabolites in hairy roots.Materials and Methods:P. multiflorum hairy root were mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Obtained results indicated the 21st day of culture growth as the most effective day for starting elicitation. The growth profile of E. prostrata (L.) L. hairy roots resemble Polygonum multiflorum hairy roots where it was found that the ideal time for the induction of anthraquinones was between the 18th and 21st days of elicitation (Huang et al 2014 ). Similarly, studies have reported the 21st day of elicitation as the end of the exponential growth phase of Artemisia annua hairy roots (Sivakumar et al 2010 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obtained results indicated the 21st day of culture growth as the most effective day for starting elicitation. The growth profile of E. prostrata (L.) L. hairy roots resemble Polygonum multiflorum hairy roots where it was found that the ideal time for the induction of anthraquinones was between the 18th and 21st days of elicitation (Huang et al 2014 ). Similarly, studies have reported the 21st day of elicitation as the end of the exponential growth phase of Artemisia annua hairy roots (Sivakumar et al 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eclipta prostrata (L.) L. produces phenolic acids such as chlorogenic acid and its derivative 3,5-di- O -caffeoylquinic acid (3,5-diCQA) (Lee et al 2010 ). Chlorogenic acid and its derivatives have demonstrated several biological activities, such as antioxidant, antibiosis, anti-inflammatory, antivirus, and antitumor activities (Huang et al 2014 ; Ali et al 2017 ; Liu et al 2018 ; Devrnja et al 2020 ). More recently, studies by molecular docking using a serine-type protease (Mpro), a SARS-CoV-2 virus polyprotein, showed that the obtained binding energies of 3,5-diCQA were closed to remdesivir (antiviral compound), indicating stronger binding to Mpro protein and promising antiviral compounds that could treat Covid-19 (Shah et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…As with cell cultures, secondary metabolite production can often be enhanced through optimized growth conditions or by using elicitors, and through metabolic engineering by transferring heterologous genes with engineered A. rhizogenes strains (Georgiev et al, 2012). Recent research on the production through hairy roots of lignans (Wawrosch et al, 2014), steroids (Doma et al, 2012), anthraquinones (Huang et al, 2014), or alkaloids (Pandey et al, 2014) clearly indicates that optimized hairy root culture systems can be used for the sustainable biotechnological production of biologically active compounds. Regarding the commercial application, the Swiss company ROOTec Bioactives AG (http://www.rootec.com) has developed an optimized bioreactor system for large-scale cultivation of hairy roots with potential to produce a number of pharmacologically active compounds (Table 6).…”
Section: Approaches For Resupply Of Pharmacologically Active Plantmentioning
confidence: 99%
“…Some of the advantages provided by hairy root cultures include high growth rates without the need for plant growth regulators, genetically and biochemically stable cultures, and a similar capacity for production of secondary metabolites than cell suspension cultures (Guillon et al 2006;Georgiev et al 2012;Mora-Pale et al 2014). A wide range of natural products has been produced using this system, including lignans, steroids, anthraquinones and alkaloids (Doma et al 2012;Huang et al 2014;Pandey et al 2014;Wawrosch et al 2014). However, metabolite 1 3 production requires that the compound of interest be one that is normally synthesized within the roots of the source plant, so this limits the versatility of the hairy root system (Ochoa-Villarreal et al 2016).…”
Section: Alternatives To In Vitro Plant Culturementioning
confidence: 99%